Effects of Feeding Flaxseeds and Rapeseeds on Milk Fatty Acid Composition in Crossbred Dairy Cattle - Bhavsar, Maitri Y.; Pandya, Paresh R.; Patel, Yogesh G.; Shah, Shailesh V.; Bhavsar, Prakrutik P. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Effects of feeding oil seeds on fatty acid profile of milk fat was studied on fifteen multiparous HF × Kankrej dairy cows (15 DIM) fed with three experimental diets, viz., T1: control, Total Mixed Ration (TMR) without oil seeds; T2: TMR with ground flaxseeds @ 4.5% and T3: TMR with ground rapeseed @ 4.5%. The experimental TMRs were offered along with 15 kg green cereal fodder as per the guidelines of ICAR standards for 120 days. The milk samples were collected at the end of the experiment for fatty acid analysis. The results revealed significant (p
Keywords: Dairy cows; Fatty acid composition; Milk; Omega3 fatty acids; Unsaturated fatty acids